Superposed remanent magnetization and magnetic fabric in Triassic carbonates of Tethys Himalaya (Jomsom area, Nepal): chronological and tectonic implications (Journal of Nepal Geological Society, 2024)
Carbonates from three sections in Tamba Kurkur and Mukut Formations near Jomsom in Nepal were investigated for natural remanent magnetization (NRM) and anisotropy of magnetic susceptibility (AMS). NRM comprises up to three components: a recent field component (RF) residing on magnetite/maghemite (soft coercivity: